Peranan Bermain Puzzle Dalam Upaya Meningkatkan Kemampuan Kerjasama Anak Usia Dini - Nirwana Nirwana; Nasaruudin R Nasaruudin R; Muhammad Yusri; Nur Asriani (Universtas Negeri Makassar, 2022)
The purpose of this study was to determine the ability of children to cooperate through playing puzzle activities. This research is a classroom action research. This research was conducted collaboratively by teachers and researchers in the classroom. The main subjects in this study were children aged 4-5 years. Data collection techniques using observation and documentation techniques. The analysis was carried out using qualitative and quantitative descriptive approaches, namely the data obtained were converted into presentation form. Based on the results of research and discussion, it can be concluded that through puzzle playing activities, children's ability to work together can be increased.